Impact of high moisture conditions on the serviceability performance of wood plastic composite decks. (5th August 2016) - Machado, José S.; Santos, Sara; Pinho, Fernando F.S.; Luís, Fábio; Alves, Ana; Simões, Rita; Rodrigues, José Carlos
Abstract: Wood plastic composites (WPCs) are being increasingly used as alternatives to wooden decks. In the present study, it was verified the potential loss of stiffness of WPC deck boards as a result of moisture intake. It was also assessed the importance of moisture intake in the fulfilment of serviceability limit states. For these purposes, three different types of commercial WPC decks were studied, with high (WPCH), medium (WPCM) and low (WPCL) expected mechanical performance. Different experimental designs were followed to simulate full exposure to outdoor conditions and the effect of possible internal stress due to differential shrinkage and the swelling behaviour of fibres and the matrix. The results indicate a high loss of bending modulus of elasticity due to water absorption (between 40 and 50%) and shrinkage/swelling movements (between 22 and 29%). This level of stiffness loss has a direct impact on ensuring the compliance to the serviceability limit states. A strong negative linear relationship between water absorption and the loss of bending stiffness was established, which can be a helpful tool to assist manufacturers in defining the application rules and ensuring the expected service life of their products. Graphical abstract: Highlights: Wood plastic composites show a significant stiffness loss when exposed to moisture or soaking/freezing/drying cycles Loss of modulus of elasticity increases linearly as water intake increases Water intake by wood plastic composites exposed to outdoor climate can jeopardize serviceability limit state criterion ATR-FTIR and analytical pyrolysis are efficient tools for the chemical characterization of wood plastic composites